Reconstruction of the Abolition of Compensation Pay-ments Towards Justice for Convicts - Aji Sumbara; Achmad Faishal; Suprapto Suprapto (International Forum of Researchers and Lecturers, 2026)
This study explores the reconstruction of the abolition of compensation payments to foster justice for convicts, specifically evaluating the intersection between Law No. 31 of 1999 and Law No. 20 of 2001. The research addresses the persistent legal dilemma where state loss recovery mechanisms often overlook the fundamental rights and socio-economic realities of prisoners. Under the current regime, the imposition of substitute imprisonment for unpaid financial obligations is perceived as a